Applications of Microscope-Integrated Indocyanine Green Videoangiography in Cerebral Revascularization Procedures - Cavallo, Claudio; Gandhi, Sirin; Zhao, Xiaochun; Belykh, Evgenii; Valli, Daniel; Nakaji, Peter; Preul, Mark C.; Lawton, Michael T. (Frontiers in Surgery, 2019)
Indocyanine green videoangiography (ICG-VA) is a near-infrared range fluorescent marker used for intraoperative real-time assessment of flow in cerebrovascular surgery. Given its high spatial and temporal resolution, ICG-VA has been widely established as a useful technique to perform a qualitative analysis of the graft patency during revascularization procedures. In addition, this fluorescent modality can also provide valuable qualitative and quantitative information regarding the cerebral blood flow within the bypass graft and in the territories supplied. Digital subtraction angiography (DSA) is considered to be the gold standard diagnostic modality for postoperative bypass graft patency assessment. However, this technique is time and labor intensive and an expensive interventional procedure. In contrast, ICG-VA can be performed intraoperatively, with no significant addition to the total operative time and when used correctly, can accurately diagnose an immediate occlusion. Such time-sensitive ischemic injury detection is critical for flow re-establishment through direct surgical management. In addition, ICG has an excellent safety profile with minimal adverse events reported in the literature. This review aims to provide an outline of the chemical behavior, technical aspects and clinical implications of this tool as an intraoperative adjunct in revascularization procedures.